2017
DOI: 10.12669/pjms.333.12355
|View full text |Cite
|
Sign up to set email alerts
|

CT findings and features of postoperative abdominal infection patients with pancreatic carcinoma

Abstract: Objective:To investigate the values of Computed Tomography (CT) in diagnosing postoperative pancreatic surgeryabdominalinfection and its efficacy and to provide a reasonable method for the diagnosis of abdominal infection.Methods:Seventy-two patients who were confirmed as resectablepancreatic carcinoma by physical examination, CT, positron emission tomography (PET)/CT, endoscopic retrograde cholangiopancreatography (ER-CP), endoscopic ultrasonography and mesenteric angiography and were admitted to the Binzhou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Clinical symptoms indicative of POPF cases include abdominal pain, fever, purulent discharge, and inflammatory markers in blood tests. Computed tomography (CT) is the most useful modality for screening of abdominal events during DP including abdominal abscess, free air, inflammation, and bleeding [5][6][7], and has often revealed peripancreatic fluid collection (FC) postoperatively [8][9][10]. Some FCs require invasive treatments if a high amylase level is demonstrated on reaspiration, because it indicates delayed pancreatic fistula [11], while other FCs do not cause any clinical problems and can go untreated.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms indicative of POPF cases include abdominal pain, fever, purulent discharge, and inflammatory markers in blood tests. Computed tomography (CT) is the most useful modality for screening of abdominal events during DP including abdominal abscess, free air, inflammation, and bleeding [5][6][7], and has often revealed peripancreatic fluid collection (FC) postoperatively [8][9][10]. Some FCs require invasive treatments if a high amylase level is demonstrated on reaspiration, because it indicates delayed pancreatic fistula [11], while other FCs do not cause any clinical problems and can go untreated.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) scan is considered the diagnostic gold standard for both secondary and ongoing peritonitis, with diagnostic sensitivity of 97.2% [36]. Laparatomy has been considered one of the most routine diagnostic techniques for postoperative intra-abdominal sepsis [37]. However, this technique presents the risk of the development of acute abdominal compartment syndrome (ACS), recognized by peritonitis, capillary leakage, and fluid resuscitation [37,38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laparatomy has been considered one of the most routine diagnostic techniques for postoperative intra-abdominal sepsis [37]. However, this technique presents the risk of the development of acute abdominal compartment syndrome (ACS), recognized by peritonitis, capillary leakage, and fluid resuscitation [37,38]. Documented data reported that when CT and abdominal ultrasound are not available, diagnostic peritoneal lavage may be useful for the diagnosis of postoperative intra-abdominal sepsis [39].…”
Section: Literature Reviewmentioning
confidence: 99%